2013
DOI: 10.1016/j.bbamcr.2012.10.002
|View full text |Cite
|
Sign up to set email alerts
|

The chloroplast protein import system: From algae to trees

Abstract: Chloroplasts are essential organelles in the cells of plants and algae. The functions of these specialized plastids are largely dependent on the ~3000 proteins residing in the organelle. Although chloroplasts are capable of a limited amount of semiautonomous protein synthesis - their genomes encode ~100 proteins - they must import more than 95% of their proteins after synthesis in the cytosol. Imported proteins generally possess an N-terminal extension termed a transit peptide. The importing translocons are ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
158
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(160 citation statements)
references
References 226 publications
2
158
0
Order By: Relevance
“…Unfortunately, without any additional data, these existing prediction tools are the best we have to predict Hsp70 binding. Multiple Chaperones May Drive Translocation-Although the mechanism of protein translocation into plastids is still poorly understood (4,(62)(63)(64)(65), most current models illustrate a vectorial transfer of the TP into the organelle with the N-ter entering the stroma first and the C-ter and the mature domain remaining behind. It has also been suggested that the TP enters and is translocated via the TOC and TIC translocons as an extended linear peptide devoid of secondary structure (66 -68).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, without any additional data, these existing prediction tools are the best we have to predict Hsp70 binding. Multiple Chaperones May Drive Translocation-Although the mechanism of protein translocation into plastids is still poorly understood (4,(62)(63)(64)(65), most current models illustrate a vectorial transfer of the TP into the organelle with the N-ter entering the stroma first and the C-ter and the mature domain remaining behind. It has also been suggested that the TP enters and is translocated via the TOC and TIC translocons as an extended linear peptide devoid of secondary structure (66 -68).…”
Section: Discussionmentioning
confidence: 99%
“…The predicted proteome of Arabidopsis plastids ranges from 1000 to approximately 3500 proteins [11], but plastid genomes only encode for 60 (higher plants) to 200 (red algae) protein-coding genes in the organelle's DNA [12]. The remaining plastid proteins (more than 90%) are encoded in the nucleus, synthesized as precursor proteins on cytosolic ribosomes and imported from the cytosol through the plastid-specific protein translocon machinery (reviewed in [13][14][15]). Because plakobranchids do not sequester algal nuclei, which can however be ingested for a short time during feeding [16], and because some proteins in higher plant chloroplasts can have turnover rates on the order of 30-120 min [17][18][19], it has been widely assumed that sequestered plastids of plakobranchids also require imported proteins to remain photosynthetically active.…”
Section: Introductionmentioning
confidence: 99%
“…Tic110 is conserved from glaucophytes, red algae to flowering plants and is almost always encoded by a single gene, except in organisms like Physcomitrella patens in which the entire genome was recently duplicated (Kalanon and McFadden, 2008;Shi and Theg, 2013). We cloned and expressed Tic110 homologues from several flowering plants for crystallography studies, but without success.…”
Section: Sequence Analyses Of Tic110 From Cyanidioschyzon Merolaementioning
confidence: 99%